Novel approaches for strengthening human fear extinction: The roles of novelty, additional USs, and additional GSs - Lipp, Ottmar; Waters, A.M.; Luck, Camilla; Ryan, K.M.; Craske, M.G. (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Since Watson and Rayner's (1920) initial demonstration that human fear can be learned by means of Pavlovian conditioning, neuroscientific and behavioral studies have provided a thorough understanding of fear acquisition. Less is known about the manner in which we can harness insights from Pavlovian conditioning research to reduce fears and, most importantly, make the reduction of fear lasting and resistant against relapse. The current paper reviews three manipulations that have shown promise in achieving a reduction of conditional fear that is more resistant to relapse than is the reduction of conditional fear after standard extinction: novelty-facilitated extinction training, presentation of conditional-unconditional stimulus pairings or of unpaired unconditional stimuli during extinction, and extinction with additional stimuli that are similar to the original conditional stimuli. It summarizes past research involving human and non-human animal subjects and highlights knowledge gaps in the current literature. Moreover, it discusses potential mechanisms that mediate the reduction of fear seen as a result of these manipulations in an attempt to enhance our understanding of what renders fear extinction less vulnerable to the known pathways to fear relapse. It is hoped that this review will contribute to the achievement of the goal that was denied to Watson and Rayner, the development of experimental techniques that can be utilized to remove conditioned emotional responses permanently.